Begriff und räumliche Struktur von Industriekombinaten in Japan - Flüchter, Winfried (ERDKUNDE, 1976)
The Japanese industrial combine is a complex of modern, raw material based, large scale plants, which is carefully planned by the central government with the cooperation of private industry. For reasons of efficiency it consists of integrated units (integrated steel works, petro chemical-, aluminium-, food-combine), and is usally geographically and functionally related to oil and energy industries. Extensive coastal areas with deep water harbours provide optimal transport facilites. As for the micro location, new land reclaimed from the sea (“filled areas or “umetate-chi) is typical and offers many advantages over the simple coast site. Also so called “dug-in harbours (“horikomi-ko) are growing in significance.